Ratusz i zabudowa śródrynkowa z czasów staropolskich w Bydgoszczy. Studium historyczne (Kronika Bydgoska, 2010)
The City Hall in the Market Sąuare, being the seat of the city council and jury, was mentioned for the first time in 1446. Maybe it was a brick structure already at that time, maybe only around 1519, when master builder Jan brought from Gdańsk coffined a part of the City Hall rooms. No matter how it was, preserved till the 19th century, the City Hall was a Gothic two-level building, with a basement, a steep gable roof covered with roofing tiles, and with decorative step gables from the north and the south. Its measurements were 26.11 m x 14.06 m. In 1600, it was decorated with a lofty tower located inside the City Hall building, within the municipality walls of its north- eastem corner. In the 17th-18,h centuries, two two-level buildings to be used by municipal servants and municipal writer were added to the City Hall from the northem side. In these centuries, the City Hall cellars featured a municipal inn and a prison, whereas the ground and first floors a hall, custody, room, court room, “medium” room, registry, archive, and a vault. The City Hall was consumed by fire in 1708 and 1756, but it was ąuickly reconstructed each time. In spite of this, it was deteriorating, and thus it was left in 1787, and completely pulled down in the years 1812-1813.Already before 1568, first trade-residential stands were added to the City Hall. In 1600 and in the next years, there were 15 stands, including 13 brick ones. They had cellars, stands on the ground floor, and residential rooms on first floors. They were liąuidated gradually starting from the 1780’s to 1829. In the neighbourhood of the City Hall, in the market sąuare, at least starting from the 15th century, there were wooden, provisional market stands and stalls for the sale of meat, bread and shoes. Depending on the time, the number of these structures was from a dozen or so to a few dozen. Municipal scales and public wells found their place in the market sąuare as well. A wooden water-supply system provided water to the wells starting from the 16lh century.